The corporate social responsibility–financial performance link in the U.S. restaurant industry: Do economic conditions matter? - Lee, Seoki; Singal, Manisha; Kang, Kyung Ho (International journal of hospitality management, 2013)
This study examines the role played by economic conditions (recessionary periods) on the link between corporate social responsibility (CSR) and corporate financial performance (CFP) in the U.S. restaurant industry. The choice of industry setting is based on the fact that the restaurant industry is subject to consumer discretionary expenditures and is thus highly sensitive to the state of the economy. This study further examines the relationship between CSR and CFP by dichotomizing CSR activities based on whether they are related to the firm's core operations or not, thus parsing out the effect of operations-related (OR) and non-operations-related (Non-OR) CSR activities, providing a more nuanced explanation of how some CSR activities may be more beneficial than others, to firm value in hard economic times.